Penerapan Online Sigle Submission (OSS) Dalam Meningkatkan Kualitas Pelayanan Publik Pada DPMPTSP Provinsi Sumatera Utara - Juwita Dewi Br Pohan; Muhammad Yafiz (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2023)
Online Single Submission is an electronically integrated business permit issued by the OSS institution in order to accelerate the business permit process. In Indonesia, licensing is actually the main obstacle for business actors. Too much bureaucracy, a lot of time, costs and the addition of many unofficial fees, make business people think about registering their business. These problems make the licensing system unhealthy and continue to recur from year to year. The implementation of licensing services through the Online Single Submission (OSS) system at the DPMPPTSP of North Sumatra Province can be considered less than satisfactory, as it still encounters issues. Specifically, business operators may not fully comprehend or utilize internet-based services. This research aims to assess the quality of public services provided through the Online Single Submission (OSS) system at DPMPTSP North Sumatra Province. The research employs a descriptive method with a qualitative approach. The findings indicate that the quality of public services through the Online Single Submission (OSS) system at the DPMPPTSP of North Sumatra Province is generally good but not yet optimal. It is recommended that the DPMPPTSP of North Sumatra Province should actively engage in outreach efforts to educate the public about the utilization of the Online Single Submission (OSS) system, allowing individuals to register their permits independently, without reliance on intermediaries or third parties.